Cyclosporine A Regulates Influenza A Virus-induced Macrophages Polarization and Inflammatory Responses by Targeting Cyclophilin A - Bai, Xiaoyuan; Yang, Wenxian; Li, Heqiao; Zhao, Yuna; Fan, Wenhui; Zhang, He; Liu, Wenjun; Sun, Lei (Frontiers in Immunology, 2022)
Cyclosporine A (CsA) is an immunosuppressive drug that suppresses T cell responses and is broadly used in transplantation. Its immunosuppressive action is closely linked to its binding of cyclophilin A (CypA), which widely distributed in different cell types. CsA also regulates the functions of innate immune cells, but the mechanism remains elusive. Here, we investigate the role of CsA in regulating macrophages polarization in influenza A virus-infected mice and mouse bone marrow-derived macrophages. CsA downregulates pro-inflammatory cytokines expression and upregulates anti-inflammatory cytokines expression. Mechanically, CsA decreases the polarization of macrophages into pro-inflammatory M1 phenotype and increases the polarization of macrophages into anti-inflammatory M2 phenotype. Further studies show that CsA regulates macrophages polarization-associated IFN-γ/STAT1 and IL-4/STAT6 signaling pathways. Meanwhile, all these roles of CsA are eliminated when CypA is absent, suggesting that CsA regulates macrophages polarization and inflammatory responses depend on its binding to CypA. Collectively, these results reveal a crucial mechanism of CsA in attenuating IAV-induced inflammatory responses by a switch in macrophages polarization.